NGO contributions to community health and primary health care: Case studies on BRAC (Bangladesh) and the Comprehensive Rural Health Project, Jamkhed (India) - Chowdhury, A. Mushtaque R.; Perry, Henry B. (Oxford University Press, 2022)
This article was published in Global Public Health by Oxford University Press [Oxford University Press Copyright © Oxford University Press 2020.] and the definite version is available at: https://doi.org/10.1093/acrefore/9780190632366.013.56 The Journal's website is at: https://oxfordre.com/publichealth/view/10.1093/acrefore/9780190632366.001.0001/acrefore-9780190632366-e-56